Toward the Development of a Uranium-Based Redox-Flow Battery - Waldschmidt, Pablo; Jori, Nadir; Riedhammer, Judith; Heinemann, Frank Wilhelm; Meyer, Karsten (Chemsuschem, 2025)
An all-uranium-based electrochemical cell consisting of simple [UIV/V(tBuacac)4]0/+ and [UIII/IV(N(SiMe3)2)4]−/0 complexes as anolyte and catholyte species was constructed with a cell voltage of 2.2 V. The [UIV(tBuacac)4] (1) and [UIV(N(SiMe3)2)4] (2) complexes have favorable properties for redox-flow-battery applications, including reversible redox chemistry, relatively high stability toward electrochemical cycling, and high solubility in common organic solvents. The [UIII/IV(N(SiMe3)2)4]−/0 complexes were first isolated and characterized by Schelter et al., and performed well in electrochemical studies due to the comparably low reduction potential of −2.05 V vs. Fc/Fc+ to the reduced uranium(III) species. Treatment of conveniently accessible 1 with AgSbF6 allowed the isolation of [UV(tBuacac)4][SbF6] (3), which is the active catholyte species generated during cell charging. Galvanostatic cycling with charging and discharging at currents of 20 and 5 μA, respectively, was performed in a two-compartment static H-cell with high-surface-area carbon fiber electrodes to achieve a potential of 2.2 V. The success of this 1||2 cell-provides a promising entry point to a potential future class of uranium-based, nonaqueous redox-flow-battery electrolytes, not for use in personal devices but incorporated into underground energy storage systems, where weight and radioactivity levels are not an issue and where this abundant waste material could find new application.
CRIS-Team Scopus Importer:2025-12-19
Keywords: electrochemistry; f-block; nonaqueous redox-flow batteries (NARFBs); redox-flow battery (RFB); uranium